PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA PADA SISWA SD BERDASARKAN TAHAPAN POLYA - Rauza, M. Yahdi; Marta, Rusdial; Zulhendri, Zulhendri; Fadhilaturrahmi, Fadhilaturrahmi; Aprinawati, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This problem iss motivated by the low problem solving abilities of students in completing mathematics story promblems at SDM 002 Penyasawan, Kampar sub-district, Kampar district. One solution to overcome this problem is apply the Polya stage. The aim of this research is to describe the application of the Polya stages to improve problem solving abilities. This research method is classroom action research (PTK) which is carried out in two cycles. Each cycle concists of two meetings and four stages, namely planning, implementation, observation, reflection. And the implementation time is October 2025. The subjects of this research were 20 grade 5 students, consisting of 10 boys and 10 girls. Data collection techniques include observation sheets, tests, documentation. The result of the research can be concluded that the level of problem solving wuth the 5th grade the Polya stage at SDM 002 Penyasawan in cycle I is quite low with an average of 69. Furthermore, out of 20 students, only 12 students completed the classical completion with 60%. While in cycle II it was good enough with an average of 84.25 out of 20 students, only 2 students did not complete tthe classical completeness of 90%. Thus it can be concluded that using the Polya stages can improve the problem solving abilities of the grade 5 students at SDM 002 Penyaswan.